Optimizing Fundamental Mathematics Concepts for Middle School Students at Al Ulum Integrated Islamic School through Innovative Teaching Methods - Lubis, Muhammad Arif; Dalimunthe, Doli Muhammad Jafar; Siringoringo, Yan Batara Putra; Lubis, Andrew Satria (Talenta Publisher, 2023)
The concept of innovative learning has become a major focus in today's education landscape. Innovative learning places an emphasis on relevant strategies and methods to address educational challenges. Two methods that play a significant role in innovative learning are Problem Based Learning (PBL) and Discovery Learning (DL). PBL centers on problem-solving based on real-life situations, while DL involves everyday experiences in finding solutions. At Al Ulum Integrated Islamic Middle School, the primary issue at hand is a high number of students receiving mathematics scores below the Minimum Mastery Criteria (KKM). Contributing factors include unengaging conventional teaching methods, leading to student boredom in mathematics classes. To address this problem, the PBL and DL methods are considered appropriate solutions. Furthermore, the implementation of this innovative learning concept is supported by information technology, both visually and non-visually, as well as the use of teaching aids to aid students in better understanding mathematical concepts. The implementation of the innovative learning concept is expected to resolve the challenges faced at Al Ulum Integrated Islamic Middle School. An evaluation will be conducted, and the outcomes will be published in Abdimas Talenta and online media. These steps are anticipated to provide sustainable benefits for both students and educators at the school.